Assessment of Personality for Influencing Team Dynamics - Ghimire, Manish (Journal of UTEC Engineering Management, 2023)
DOI: https://doi.org/10.36344/utecem.2023.v01i01.009 Personality and team dynamics are closely related and can have a significant impact on the effectiveness of a team. Having a diverse range of personalities on a team can bring new ideas and solutions, but it can also lead to conflicts if team members have difficulty communicating or working together effectively. Personality and team dynamics play an important role in determining the effectiveness of a team. A diverse range of personalities can bring new ideas and solutions, but it can also lead to conflicts if team members have difficulty communicating or working together effectively. This is a literature based research to find team dynamics under different personality. The development of innovative solutions to complex problems in the field of information systems (IS) has become increasingly challenging. In order to meet these challenges, many organizations have adopted the use of cross-functional teams in their IS development process. These teams consist of both users, such as accountants and salespeople, and IS professionals, such as systems analysts and programmers. The goal of these teams is to work together effectively in order to produce successful systems. The team-building literature suggests that teams should have high levels of satisfaction with their performance, but in reality, this is not always the case. This suggests that there may be challenges in effectively implementing teams in the IS development process.